2017
DOI: 10.1039/c7dt01647f
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of metallic silver coatings by Aerosol Assisted MOCVD using two new silver β-diketonate adduct metalorganic precursors

Abstract: This work reports two new silver metalorganic precursors for the chemical vapor deposition of Ag metallic coatings. Both precursors are based on β-diketonate adducts, namely, Ag(hfac)(L) (H-hfac = 1,1,1,5,5,5-hexafluoro-2,4-pentanedione), where L is 1,10-phenanthroline (phen) or 2,5,8,11-tetraoxadodecane (triglyme). Using these ligands, the designed precursors have better solubility in alcoholic solvents and are less toxic and costly than previously reported ones. The new precursors have been characterized and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…19,20 Our previous studies have shown that glymes play a pivotal role in stabilizing complexes with the desired thermal properties for MOCVD applications. 21,22 Glymes often behave like crown ethers in terms of coordinating/solvating ions of the alkaline-earth, 23,24 the transition 25,26 and the rare-earth metals 22,27 through oxygen-ion complexation i.e. chelating properties, which leads to thermally stable and volatile adducts.…”
Section: -17mentioning
confidence: 99%
“…19,20 Our previous studies have shown that glymes play a pivotal role in stabilizing complexes with the desired thermal properties for MOCVD applications. 21,22 Glymes often behave like crown ethers in terms of coordinating/solvating ions of the alkaline-earth, 23,24 the transition 25,26 and the rare-earth metals 22,27 through oxygen-ion complexation i.e. chelating properties, which leads to thermally stable and volatile adducts.…”
Section: -17mentioning
confidence: 99%
“…[18][19][20] Potassium ion has a large ionic radius (r 6-coord = 1.51 Å), [13] which is responsible for interesting coordination moieties giving rise, in function of the coordinating ligands to extended oligomeric or polymeric network. [21][22][23] Former studies have shown that glymes play a crucial role in stabilizing complexes of alkaline-earth, [24][25][26][27][28] transition [29,30] and rare-earth metals [31,32] through oxygen-ion complexation. Recently, we have also devoted our attention to alkali metals, namely Li [33] and Na.…”
Section: Introductionmentioning
confidence: 99%
“…15–17 Among these materials, silver nanoparticles have been widely used for their simple and versatile syntheses and high antibacterial yield. 18–21…”
Section: Introductionmentioning
confidence: 99%